Pay or not to Pay Dividends: Company Policy and Investor Expectations - Kanwal Iqbal Khan; Muhammad Mudasar Ghafoor; r, Muhammad Sheeraz; Shahid Mahmood (The Lahore Journal of Business)
This paper attempts to understand the linkage of dividend decisions and investors’ perceptions within the context of the Pakistani corporate sector. It is intended to proffer new evidence for designing dividend policies that satisfies investors’ perceptions. Data are collected from individual investors by using questionnaires to obtain opinions about essential factors, patterns, processes and preferences for cash dividends. Results indicate that stability in the rate of dividend, compatibility with the inflation rate and continuity of dividend payment are the topranking factors for investors. Stock dividends are preferred by Pakistani investors if their company is not paying cash dividends, and share buy-back decisions are taken negatively. The theoretical explanation for preferring dividends indicates that Pakistani investors support dividend signaling theory, agency cost, clientele effect, asymmetric information effect, tax effect and rational expectation models. That is why it exhibits a positive relation between dividends and investors’ perception. The contributions and recommendations for further studies are also addressed.